Modeling the Effective Connectivity of the Visual Network in Healthy and Photosensitive, Epileptic Baboons - Szabó, C. Ákos (Brain Struct Funct, 2015)
The baboon provides a model of photosensitive, generalized epilepsy. This study compares cerebral blood flow (CBF) responses during intermittent light stimulation (ILS) between photosensitive (PS) and healthy control (CTL) baboons using H(2)(15)O-PET. We examined effective connectivity associated with visual stimulation in both groups using structural equation modeling (SEM). Eight PS and six CTL baboons, matched for age, gender and weight, were classified on the basis of scalp EEG findings performed during the neuroimaging studies. Five H(2)(15)O-PET studies were acquired alternating between resting and activation (ILS at 25 Hz) scans. PET images were acquired in 3D mode and co-registered with MRI. SEM demonstrated differences in neural connectivity between PS and CTL groups during ILS that were not previously identified using traditional activation analyses. First-level pathways consisted of similar posterior-to-anterior projections in both groups. While second-level pathways were mainly lateralized to the left hemisphere in the CTL group, they consisted of bilateral anterior-to-posterior projections in the PS baboons. Third- and fourth-level pathways were only evident in PS baboons. This is the first functional neuroimaging study using to model the photoparoxysmal response (PPR) using a primate model of photosensitive, generalized epilepsy. Evidence of increased interhemispheric connectivity and bidirectional feedback loops in the PS baboons represents electrophysiological synchronization associated with the generation of epileptic discharges. PS baboons demonstrated decreased model stability compared to controls, which may be attributed to greater variability in the driving response or PPRs, or to the influence of regions not included in the model.